The muses - Kinley, Kylie (Kansas State University, 2013)
This project is the first three chapters of a young adult novel, The Muses. Lily Bellows is singled out in infancy to become one of the Muses, humans given supernatural powers through enchanted golden masks. The six Muses (Faith, Wisdom, Pride, Obedience, Courage, and Desire) are telepathically linked to Illyria’s king so that he is better able to manage his emotions and thus rule more efficiently. Lily is destined to be the Muse of Faith, but her parents fake her death and keep her abilities secret until she heals her village of a deadly plague and the Muses consequently return for her. As Lily struggles to master fighting arts, healing skills, and the ability to manipulate emotions, she must also befriend the moody Prince Connor who will one day share her consciousness, and she must untangle the complicated feelings she has for Connor’s illegitimate brother, Ronan. While Lily’s fellow Muse initiates have been training since infancy, Lily joins them as a teenager, and she finds it nearly impossible to give up her family, her dreams and her individuality so she can make Prince Connor into a better king. When she has the chance to break the oath she swore to serve her country as its Muse of Faith, she must choose between power and individuality and determine whether she must submit to her destiny or create her own.
Keywords: Novel; Fantasy; Young adult; Literature (0401)